Порівняння ефективності підходів Map-Reduce і акторної моделі при розв’язанні завдань з високою зв'язністю вхідних даних на прикладі задачі оптимізації рою часток - Ларін, В.О.; Провотар, О.І. (Проблеми програмування, 2021)
Показані приклади класу розподілених паралельних задач зі зв'язаними компонентами вхідних даних в рамках моделі Map-Reduce. Виконано порівняння ефективності подібної задачі на прикладі задачі рою часток в рамках моделі Map-Reduce (на основі фреймворку Spark) і акторної моделі з підтримкою спільної пам'яті (на основі Strumok DSL). Оцінено перспективи використання гібридної акторної моделі для інших подібних задач. The paper defines the notion of distributed problems with bounded input components. Particle Swarm Optimization problem is shown to be an example of such a class. Such a problem's implementation based on the Map-Reduce model (implemented on the Spark framework) and an implementation based on an actor model with shared memory support (implemented on Strumok DSL) is provided. Both versions' performance assessment is conducted. The hybrid actor model is shown to be an order of magnitude more effective in time and memory efficiency than Map-Reduce implementation. Additional optimization for the hybrid actor model solution is proposed. The prospects of using the hybrid actor model for other similar problems are given.